Assentamentos Precários e Vulnerabilidade Socioambiental: O Caso da Ocupação Valinhos II, Passo Fundo, RS: Precarious Settlements and Socio-environmental Vulnerability: The Case of the Valinhos II Occupation, Passo Fundo, RS - Garbin, Lívia; Tiecher , Francieli (ANAP Brazil, 2025)
Objective – This article aims to analyze basic sanitation conditions in the Valinhos II Occupation, in Passo Fundo/RS, and to present technical-urban proposals developed within the scope of the extension program of Atitus Educação College. Methodology – The research adopted a qualitative approach, based on literature review, technical visits, field surveys, participatory workshops with residents, and the development of proposals. Originality/Relevance – The study contributes to the discussion on urban precariousness and the role of educational institutions and their trained professionals in promoting sustainable solutions for cities and, consequently, for their residents. Results – The main results point to the lack of adequate basic infrastructure and the urgent need for interventions focused on sanitation, drainage, and solid waste management. Theoretical/Methodological Contributions – The study reinforces the importance of interdisciplinarity between Architecture and Engineering in formulating urban proposals in vulnerable contexts. Social and Environmental Contributions – The proposals developed offer viable and low-cost alternatives to improve the living conditions of the local population, promoting social inclusion, public health, and environmental preservation.